2006
DOI: 10.1017/s0014479705003029
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Cotton to Subsurface Drip and Furrow Irrigation in a Vertisol

Abstract: The practice and management of subsurface drip irrigation (SDI) on heavy clay soils is poorly understood. Over-irrigation can lead to excessive runoff and drainage, with associated negative environmental consequences. Experiments were conducted in 2001/2002 and 2002/2003 on cotton (Gossypium hirsutum) in a Vertisol in Australia to evaluate the effect of SDI at various application rates on cotton yield and quality, and the results were compared with those for conventional furrow irrigation. Irrigating with SDI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Similarly, other researchers (Norton and Silvertooth, 2001;Cetin and Bilgel, 2002;Bhattarai et al, 2003;Khalifa, 2006) found a substantial improvement in water use efficiency due to economizing water under drip irrigation. Various scientists (Robertson , 2006;Singh et al, 2007;Jonghan and Piccinni, 2009;Singh et al, 2010;Wei et al, 2012) also noticed water savings for the drip method of irrigation compared to the furrow method.…”
Section: Physiological Efficiencymentioning
confidence: 76%
“…Similarly, other researchers (Norton and Silvertooth, 2001;Cetin and Bilgel, 2002;Bhattarai et al, 2003;Khalifa, 2006) found a substantial improvement in water use efficiency due to economizing water under drip irrigation. Various scientists (Robertson , 2006;Singh et al, 2007;Jonghan and Piccinni, 2009;Singh et al, 2010;Wei et al, 2012) also noticed water savings for the drip method of irrigation compared to the furrow method.…”
Section: Physiological Efficiencymentioning
confidence: 76%
“…We have shown (Bhattarai et al, 2006) the advantages of subsurface drip over furrow for yield and water use efficiency of cotton in a tropical environment. Subsurface drip can also potentially offer a multitude of other advantages by minimizing the off-site movements of run-off, sediments, pesticides and nutrients (Camp et al, 1999) provided crop, soil and climate specific irrigation rates are applied.…”
Section: Introductionmentioning
confidence: 89%
“…Since agriculture is a major consumer of water for food and fiber production, it becomes critical to use efficient water delivery systems to crops, in addition to utilizing the most drought-tolerant water-efficient crops, cropping systems, tillage practices, and plant genetic materials available in sustainable crop production. Subsurface drip irrigation (SDI) is perhaps the most efficient water delivery system to roots of plants, producing crop yields equal to or greater than other irrigation methods and, in many cases, requiring less water and improved water-use efficiencies [3][4][5][6]. In regions where irrigation well capacities are low and in cases where available irrigation water is saline or where shallow water conditions are saline, SDI, compared with surface irrigation systems, offers the greatest potential to increase yields and irrigation water use efficiency [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Darusman et al [19] in Kansas with corn (Zea mays L.) and Bhattarai et al [6] in Australia with cotton also concluded that 100% crop ET replacement was not necessary to optimize plant productivity and water-use efficiency. Overirrigation can lead to oxygen deficiency, excessive runoff following a high rainfall event, and increased internal drainage that can transport nitrates and other nutrients deeper into the soil profile and ground water.…”
Section: Introductionmentioning
confidence: 99%